African Journal of Pharmacy and Pharmacology Phytochemical and efficacy study on four herbs used in erectile dysfunction: Mondia whiteii, Cola acuminata, Urtica massaica, and Tarenna graveolens - Oloro, Joseph; Julius Kihdze Tanayen, Julius; Barbra Katusiime, Barbrarbra; Lawrence Imanirampa, Imanirampa (African Journal of Pharmacy and Pharmacology, 2016)
here is a resurgence in the use of herbal medicine in the developed countries, with even much more in low developed Countries and especially for conditions such as erectile dysfunction. Studies thus need to be conducted to scientifically validate claims on certain medicinal plants reported to be efficacious in traditional medicine. This current study was conducted to determine the phytochemical composition and efficacy of four herbs Mondia whiteii (Hook. F.) roots locally called (Mulondo), Cola acuminata (P. Beauv.) fruits locally called (Engongoli), Urtica massaica (Mildbr) leaves, locally called (Engyenyi) and Tarenna graveolens (S. Moore) roots, locally called (Munywamaizi) in Runyankole which have been reported as remedies for the management of erectile dysfunction in South-western Uganda. Phytochemical screening was conducted following methods described in Kokate, Trease and Evans. Sexual function was tested using both the contact and non-contact model. Arginine was present in all the extracts. Aqueous extract of Tarenna graveolens significantly improved testosterone levels but none of the extracts had significant effects on mounting frequency. Aqueous extract of Tarrena graveolens could be useful in management of erectile dysfunction associated with hypogonadism. Key words: Erectile dysfunction, efficacy, phytochemical, testosterone, Mondia, Cola, Urtica, Tarenna.
Mondia whiteii, Cola acuminata, Urtica massaica, and Tarenna graveolens
Keywords: Erectile dysfunction; efficacy, phytochemical; testosterone; Mondia; Cola; Urtica; Tarenna